mproving Studentsâ Learning Achievement Of Science On Describing The Natures Of Light Using Demonstration And Experiment Method (Demex) For The Fifth Grader Of B Group In Sdn 1 Karanganyar - Priyanti, Priyanti (Dinamika, 2014)
he study was aimed at improving the studentsâ learning motivation and achievement ofscience on âDescribing the natures of lightâ applying two methods of demonstration andexperiment. This involved the studentsâ active participation in group works. It applied aclassroom action research conducted following the principles of Kemmis S, C TaggartR (1988) covering planning, acting, oberserving, and reflecting or evaluating. Thesestages were done to achieve the improvement target in two cycles. This was done bycollaborating with the peers as observer, supervisor and the principal of the elementaryschool, in the Education District Unit of Karanganyar, Purbalingga Regency.Based on the analysis, it can concluded that (1) the studentsâ participation andunderstanding is better; they are motivated better and actively involved in the learningactivities, (2) the studentsâ learning achievement also improves, using this method.After the cycle I, the studentsâ learning mastery was 53,12%, with an average score of68,91 and their motivation index was 71,88%. At the end of the cycle II, their masteryincreased significantly, 81,25%, and their average score was 78,13. Their motivationimproved to 84,38%. The results of the cycle II has shown that their mastery level hasexceeded the target to be more than 75% and also their learning motivation. Based onthe findings, it can be concluded that the use of Demex method in science learning ofdescribing the natures of light is effective in this research.Keywords: demex, demonstration, experiment, motivation, achievement.